Design of an Antioxidant Powder Additive Based on Carvacrol Encapsulated into a Multilayer Chitosan-Alginate-Maltodextrin Emulsion - Matiacevich, S (Elsevier B.V., 2024)
Carvacrol has demonstrated antioxidant activity; however, its high volatility and low water solubility limit its direct application in food matrices. Then, an effective encapsulation system is required to protect it. This study aimed to design and characterize a carvacrol-based additive encapsulated in a spray-dried multilayer emulsion based on chitosan/sodium alginate/maltodextrin. Spray-drying temperature of 120 °C and 3 %(w/w) maltodextrin content maximized both encapsulation efficiency (~97 %) and loading capacity (~53 %). The powder s antioxidant properties were evaluated in two food simulant media: water (SiW) and water-ethanol (SiD). The highest antioxidant activity was observed in SiW for both ABTS•+ (8.2 ± 0.3mgEAG/g) and FRAP (4.1 ± 0.2mgEAG/g) methods because of the reduced release of carvacrol in SiD vs. SiW, as supported by micro- and macrostructural observations by SAXS and microscopy, respectively. An increase from 143 to 157 °C attributable to carvacrol protection and Tg = 44.4 °C (> ambient) were obtained by TGA and DSC, respectively. FT-IR confirmed intermolecular interactions (e.g. -COO− and -NH3+) as well as H-bonding formation. High water solubility (81 ± 3 %), low hygroscopicity (8.8 ± 0.2 %(w/w), poor flowability (CI:45 ± 4), and high cohesiveness (HR:1.8 ± 0.1) between particles were achieved, leading to a powdered antioxidant additive with high potential for applications which required avoiding/reducing oxidation on hydrophilic and hydrophobic food products. © 2023